The Effect of Auditor’s Work Stress on Audit Quality of Listed Companies in Indonesia - Cliff Oliver Winoto; Senny Harindahyani (Journal of Economics, Business, and Accountancy Ventura, 2020)
Audit failure practices have been the headlines in the past decade. At the same time, auditing is associated with high stress and over-timed work. However, a concern regarding the importance of audit quality rises nowadays. This research aims to find the effect of auditor’s work stress to audit quality. Additionally, it is intended to find how the presence of certain condition, such as such as initial audit partner engagement, audit firm size, and client litigation risk, impact the effect of auditor work stress to audit quality. This research utilizes data of listed Indonesian companies during 2014 – 2016. The methodology used is multiple linear regression. This research finds that auditor’s work stress affect audit quality significantly and negatively. This finding enhances Interaction Theory, where generally in Indonesian audit profession; the increased job-demand is not balanced by good job-control and social support. However, initial audit partner engagement and big audit firm size can mitigate the effect of such stress. While client litigation risk does not affect the impact of auditor’s work stress to audit quality. This study suggests that public accounting firms pay attention to job demand, low job control, and low social support, which are elements of work stress, to improve audit quality.